Technologies of truth : cultural citizenship and the popular media - Miller, Toby (Visible evidence ;, 1998)
In a world ever more complex and media-saturated, what is the value of the truth? Here, Toby Miller provides a pithy and clear-sighted examination of how television, magazines, film, and museums influence the way our society conceptualizes such issues as citizenship, democracy, nationhood, globalization, truth, and fiction. Along the way, he explicates surprising connections between cultural objects and discourses, producing a new meeting ground for cultural, social, and political theory.